2004
DOI: 10.1242/dev.01061
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of heparan sulfate synthesis inDrosophiladisrupts the Wingless, Hedgehog and Decapentaplegic signaling pathways

Abstract: Decapentaplegic (Dpp) signaling. This contrasts with previous studies that suggested loss of ttv compromises only Hh signaling. Our results may contribute to understanding the biological basis of hereditary multiple exostoses (HME), a disease associated with bone overgrowth that results from mutations in EXT1 and EXT2, the human orthologs of ttv and sotv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
187
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(201 citation statements)
references
References 66 publications
(71 reference statements)
9
187
1
4
Order By: Relevance
“…Our recent studies have demonstrated that both Dally and Dlp are required for Hh and Dpp movement through a restricted diffusion mechanism (Belenkaya et al, 2004;Han et al, 2004b). Regarding Wg morphogen formation, several studies have shown that mutations in genes involved in HS biosynthesis lead to defects in Wg distribution in the wing disc (Baeg et al, 2001;Bornemann et al, 2004;Han et al, 2004a;Luders et al, 2003;Takei et al, 2004). We have previously shown that Dally plays a role in Wg signaling in the wing disc (Lin and Perrimon, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies have demonstrated that both Dally and Dlp are required for Hh and Dpp movement through a restricted diffusion mechanism (Belenkaya et al, 2004;Han et al, 2004b). Regarding Wg morphogen formation, several studies have shown that mutations in genes involved in HS biosynthesis lead to defects in Wg distribution in the wing disc (Baeg et al, 2001;Bornemann et al, 2004;Han et al, 2004a;Luders et al, 2003;Takei et al, 2004). We have previously shown that Dally plays a role in Wg signaling in the wing disc (Lin and Perrimon, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The Drosophila genome harbors three homologs of the mammalian EXT genes, namely, tout velu (ttv; Bellaiche et al 1998), sister of tout velu (sotv; Bornemann et al 2004;Han et al 2004b), and brother of tout velu (botv; Han et al 2004b). Mutations in either one of the three genes result in impaired HSPG biosynthesis (The et al 1999;Han et al 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the GPI-linked HSPG Dally has been shown to affect Hh signaling (Desbordes et al 2003;Han et al 2004a). Mutations in any of the three Drosophila EXT genes result in impaired Hh, Wg, and Dpp distribution and signaling (The et al 1999;Bornemann et al 2004;Han et al 2004b;Takei et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they bind to and control the biological function of signaling molecules, such as growth factors and morphogens (Allen and Rapraeger, 2003;Johnson et al, 2004;Kreuger et al, 2006). These interactions with signaling molecules underlie in part the importance of HSPGs in development (Lin et al, 1999;Galli et al, 2003;Bornemann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of HS defines its interactions with other molecules, and is largely determined by its biosynthesis (Binari et al, 1997;Bellaiche et al, 1998;Bornemann et al, 2004) and posterior enzymatic degradation by heparanase. While disruption of either process appears to disturb normal development, heparanase manipulations have mainly involved exogenous treatment of the developing embryo with bacterial heparatinase (Yost, 1992;Brickman and Gerhart, 1994;Itoh and Sokol, 1994;Walz et al, 1997).…”
Section: Introductionmentioning
confidence: 99%